Decision Making based on Ethical Values in Business Management - Evangeline Cherryl D; Kalistarosa, Aqiela; Sari, Adiva Belva; Kusumasari, Indah Respati; Hidayat N, Rusdi (Jurnal Bisnis dan Komunikasi Digital, 2025)
Decision making is at the heart of every business activity. Decisions taken not only impact the company's performance, but also various stakeholders, including employees, consumers, and society at large. In an increasingly complex and dynamic business context, it is important for decision makers to consider ethical aspects in every choice they make. This study aims to analyze how ethical values ​​can be integrated into the business decision-making process. Through literature studies and case analysis, this study identifies several ethical principles that are relevant in the business context, such as honesty, fairness, social responsibility, and sustainability. In addition, this study also discusses the various challenges faced by companies in implementing business ethics, as well as strategies that can be used to overcome these challenges. The results of the study indicate that ethical decision making can provide a number of benefits for companies, including: improving the company's reputation, increasing trust from stakeholders, reducing risks, and improving long-term performance. However, to achieve this, a strong commitment from company leaders is needed, the development of an ethically oriented organizational culture, and the existence of an effective mechanism to ensure that decisions taken are in accordance with the company's ethical values. This study concludes that ethical decision-making is not just an option, but a necessity for companies that want to achieve long-term success. By integrating ethical values ​​into every aspect of the business, companies can create added value for all stakeholders and.